The Effect of Coaching Leadership on Change Oriented Behaviors: Mediation Effect of Psychological Safety and Moderated Mediation Effect of Future Time Perspective - Tak, 진국; Lee, InWha (Korean Journal of Industrial and Organizational Psychology, 2023)
The purpose of this study is to reveal the effect of coaching leadership on psychological safety and change-oriented behavior, and how the effect differs depending on the level of future time perspective. Accordingly, the relationship between coaching leadership and change oriented behavior was examined, and the mediating effect of psychological safety in the influence of coaching leadership on change oriented behavior was confirmed. In addition, the moderating effect of future time prospects was confirmed when psychological safety affects change-oriented behavior. Finally, the moderated mediating effect of future time prospects was verified in the mediation of psychological safety in the relationship between coaching leadership and change-oriented behavior. For this purpose, data from 349 Korean office workers were collected through an online survey, and data were analyzed using SPSS 25.0 and PROCESS Macro. As a result of the study, it was verified that the relationship between coaching leadership and change-oriented behavior was significantly mediated by psychological safety and had a partial mediating effect. Both the moderating effect and the moderated mediating effect of future temporal prospects were significant. Finally, in this study, the implications, limitations, and suggestions derived from the research results were discussed.